2017
DOI: 10.1007/978-1-4939-7253-1_16
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Surface Antigen Staining of Larger Extracellular Vesicles

Abstract: Larger extracellular vesicles, microparticles (MPs) or microvesicles (MVs), especially their acquisition and characterization by flow cytometry (FACS), is increasingly in focus of clinical/translational research efforts. Several laboratories have shown that MPs/MVs might be suitable for the diagnosis and predicting prognosis in various diseases including cancer. However, FACS staining of larger extracellular vesicles (EVs) can be difficult and results potentially in false positive and inconsistent data interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The differential behaviour of ApoD and BSG upon OS is worth further analysis, since it brings interesting scenarios of stimulus-triggered protein sorting mechanisms. Upon acute stress, BSG and ApoD might follow different routes to either get internalized (ApoD) [ 12 ] or exported into plasma membrane-derived extracellular vesicles (BSG) [ 39 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differential behaviour of ApoD and BSG upon OS is worth further analysis, since it brings interesting scenarios of stimulus-triggered protein sorting mechanisms. Upon acute stress, BSG and ApoD might follow different routes to either get internalized (ApoD) [ 12 ] or exported into plasma membrane-derived extracellular vesicles (BSG) [ 39 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the size threshold of standard flow cytometers is~300 nm (see [75] for a current instrument comparison), this allows the quick measurement and quantification of MV protein expression in contrast to Exo, which have to be coupled prior to analysis to larger latex beads following a time-consuming protocol. Protocols exist for staining of single or multiple markers on plasma-derived MV for flow cytometry [76,77]. Even though flow cytometry might not allow the detection of very small MV <300 nm and thus not reproduce the whole spectrum of MV in blood, several studies have successfully demonstrated the potential of flow cytometry for measuring MV-associated cancer biomarkers, as discussed in detail below.…”
Section: Analysis Of MV In Peripheral Bloodmentioning
confidence: 99%
“… 21 Fluorescent-activated cell sorting can be used to detect MVs via conjugation with specific fluorescent antibodies. 49 , 50 In addition, electron microscopy provides direct evidence for the presence of MV structures and is more popular in the detection of MVs. 48 …”
Section: The Biogenesis and Characterization Of Mvsmentioning
confidence: 99%